Potential Gastronomy Tourist Attraction in the Area of Alun-Alun Utara Yogyakarta - Nugroho, Setyo Prasiyono; Kurniawati, Neni; Sinangjoyo, Nikasius Jonet; Islami, Mona Erytrea Nur (Technium Social Sciences Journal, 2021)
Culinary tourism happens when the tourists visit a certain tourist destination and their aim is to enjoy the traditional cuisines. Gastronomy tourism, however, happens when the gastronomy is considered as the main motive behind the people who prepare and serve the food and beverages ingredients. The aim of this research is to observe the tourist attraction of gastronomy tourism in the area of Alun-alun Utara (Northern Alun-alun) of Yogyakarta. Qualitative method was applied in this research. The research techniques were interview, documentation, observation, and literature review. The data analysis technique was done by employing the data reduction, data presentation, and conclusion. The result of the research shows that there are four potencies of tourist attractions found in this area. There are: Wedang Ronde Mbah Sulastinah, Angkringan Pendopo Lawas, Gudeg Yu Djum Wijilan, and Prince Joyokususmo’s House (Gadri Resto). In these places, the tourists are able to enjoy the dishes and listen to the stories behind the process of making/producing these dishes. There are also the story of their origins and how to cook/make these dishes as well. Those activities can be considered as the gastronomy tourist attractions.